The unlikeliness of an imminent sub-2-hour marathon: Historical trends of the gender gap in running events - Tucker, R.; Santos-Concejero, J. (International Journal of Sports Physiology and Performance, 2017)
The aim of the current study was to analyze men`s and women`s world records across the full range of running disciplines to contextualize the recent debate about the possibility of a sub-2-h marathon. The average male-female gap is currently 11.2% ± 1.0% for all running events. However, reducing the marathon time to below 2 h would produce a performance 12.9% (+1.7 SD) faster than the women`s marathon record. This gap would be greater than all current world-record differences and would also require a reversal of medium- and long-term historical trends in the men`s and women`s record differences. We therefore conclude that based on historical trends and known differences between men`s and women`s performances, the current women`s world record is not yet the equivalent of a sub-2-h marathon and, therefore, that an imminent sub-2-h marathon is implausible.